(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article is devoted to environmental and social aspects of irrigation development in Uzbekistan under climate change. Irrigation development in Central Asia, especially in Uzbekistan, is a key element for ensuring food security and sustainable agricultural development in arid climate conditions. However, this process is accompanied by significant environmental and social consequences. The article discusses the main environmental problems such as loss of water resources, reduction of biodiversity, soil salinisation and pollution of water bodies. Social impacts are also discussed, including population migration, conflicts over resources and changes in traditional ways of life. Particular attention is paid to the lack of consideration of environmental and social factors in the planning and implementation of irrigation projects, which can lead to increased negative impacts. The article emphasises the need for an integrated approach to water resources management, including adaptation to climate change, introduction of water-saving technologies and regular environmental assessments. The relevance of the article is justified by the existing need for balanced development of irrigation systems, which should take into account both the needs of agriculture and environmental protection. It is recommended to involve local communities in the process of planning and project management, as well as to conduct educational programmes to raise awareness of sustainable use of water resources.